Vivências da parteira em Acorizal – MT : saberes e experiências no cuidado com a vida - Campos, Márcia de (2017)
This is a qualitative research with a phenomenological approach, which used the Oral History of Life as a way to investigate the phenomenon to midwife as an art of caring for life. It is about making a historical record from the narratives of an accoucheuse who resides in the Acorizal town, of the Mato Grosso State (MT), Brazil, forty years ago and who helped one thousand and one hundred and six (1106) women when they were giving birth to their children. This work is to understand the knowledge and experiences of midwives in caring for women during the process of gestating and giving birth at home, and their relation with health care. We consider it relevant to investigate this experience, because dealing with the principle of health care is to create the conditions to construct a thought and practices that give account and, above all, that does not ignore all the cultural diversity, in the care of itself, of the other, and of the environment. It is worth mentioning that this study feature is justified by the need to record the participation of Sister Dagmar and the history of Acorizal town, in popular health education, in the health history of the Mato Grosso State and a notion of all Brazilian midwives’ reality. Knowledge and experiences narrated by her were, of course, experienced in the daily life of that community. The results reveal that this woman's life history is inscribed in an ancient knowledge that over time offers a significant contribution to the construction of a new knowledge in search of the humanization of relationships in the context of health. It is known that much of this knowledge was disregarded because of the hegemonic institutionalization of the biomedical and hospital centered care. In view of the diversity of the cultural universe that surrounds this knowledge, considered a practice of solidarity, we affirm that Sister Dagmar's presence in the Acorizal town, as the great caregiver, demonstrates a singular way of caring that takes into account knowledge, appointment and responsibility and she does it exactly as in her own words: “a charism and a commitment with a gift from God”